The Fourfold Gospel - Stanton, Graham (New Testament studies, 1997)
The origins and the theological significance of the fourfold Gospel raise a set of teasing questions. Why did the early Church eventually accept four partly parallel foundation documents? There is no precedent for this either in the OT Scriptures or elsewhere in earliest Christianity. Did retention of four gospels assist or hinder the early Church in the presentation of its claims concerning Jesus? No doubt to some, insistence that there were four gospels implied that there were basic flaws in the single gospels. Was the second century church's decision to bring together four separate gospels wise? What were, and what are, the theological implications of the fourfold Gospel? A critical theology cannot avoid asking these questions.